Angiotensin Type 1a Receptor Signaling Is Not Necessary for the Production of Reactive Oxygen Species in Polymorphonuclear Leukocytes. (4th December 2012) - Yamato, Fumiko; Takaya, Junji; Tsuji, Shoji; Hasui, Masafumi; Kaneko, Kazunari
Abstract : Background . Although angiotensin II (Ang II) has inflammatory effects, little is known about its role in polymorphonuclear leucocytes (PMLs). To elucidate the role of Ang II in PMLs ROS production, we examined hydrogen peroxide (H2 O2 ), one of the ROS, and NO production in AT1a receptor knockout (AT1KO) mice. Methods and Results . PMLs were analyzed from Ang II type 1a receptor knockout mice (AT1KO) and C57BL/6 wild type mice. Using flow cytometry, we studied hydrogen peroxide (H2 O2 ) production from PMLs after Staphylococcus aureus phagocytosis or phorbol myristate acetate (PMA) stimulation. Nitric oxide (NO) production in the AT1KO was low at basal and after phagocytosis. In the AT1KO, basal H2 O2 production was low. After PMA or phagocytosis stimulation, however, H2 O2 production was comparable to wild type mice. Next we studied the H2 O2 production in C57BL/6 mice exposed to Ang II or saline. H2 O2 production stimulated by PMA or phagocytosis did not differ between the two groups. Conclusions . AT1a pathway is not necessary for PMLs H2 O2 production but for NO production. There was a compensatory pathway for H2 O2 production other than the AT1a receptor.